2021
DOI: 10.1111/liv.14827
|View full text |Cite
|
Sign up to set email alerts
|

Liver chemistries in glycogenic hepatopathy associated with type 1 diabetes mellitus: A systematic review and pooled analysis

Abstract: Background & Aims Glycogenic hepatopathy (GH) in type 1 diabetes‐mellitus (T1DM) is characterized by hepatomegaly and perturbations of liver chemistries (LC) that have not been well studied. Furthermore, misdiagnosis with other hepatic complications of T1DM, such as nonalcoholic fatty liver disease, has been described. We perform a systematic review of biopsy‐proven GH reports in T1DM patients to identify LC patterns. Methods A systematic review identified reports of biopsy‐proven GH in patients with T1DM. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Signs of liver cirrhosis might be present in advanced NAFLD. proven GlyH showed that both ALT and AST are moderate-toseverely elevated in 78 and 76% of cases, with an ASTpredominant pattern and improvement when glycemic control was obtained (Haffar et al, 2021). In this pooled analysis, the median HbA1c was 12% and median BMI 21 kg/m 2 , stressing the correlation with extremely poor glycemic control, which is hardly seen any longer in current practice, but not necessarily with abdominal adiposity.…”
Section: Glycogenic Hepatopathy: Epidemiologymentioning
confidence: 65%
See 1 more Smart Citation
“…Signs of liver cirrhosis might be present in advanced NAFLD. proven GlyH showed that both ALT and AST are moderate-toseverely elevated in 78 and 76% of cases, with an ASTpredominant pattern and improvement when glycemic control was obtained (Haffar et al, 2021). In this pooled analysis, the median HbA1c was 12% and median BMI 21 kg/m 2 , stressing the correlation with extremely poor glycemic control, which is hardly seen any longer in current practice, but not necessarily with abdominal adiposity.…”
Section: Glycogenic Hepatopathy: Epidemiologymentioning
confidence: 65%
“…One study compared T1D patients with and without hepatopathy (based on imaging, not on histology) and did not find significant correlations between ALT and AST levels and aberrant ultrasonographic imaging, but hyperechogenicity was indeed correlated to poor glycemic control ( Aydın et al, 2019 ). One pooled analysis of 192 documented cases of histologically proven GlyH showed that both ALT and AST are moderate-to-severely elevated in 78 and 76% of cases, with an AST-predominant pattern and improvement when glycemic control was obtained ( Haffar et al, 2021 ). In this pooled analysis, the median HbA1c was 12% and median BMI 21 kg/m 2 , stressing the correlation with extremely poor glycemic control, which is hardly seen any longer in current practice, but not necessarily with abdominal adiposity.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory workup often presents mild to moderate elevation in liver aminotransferases, with a predominant elevation of glutamate oxaloacetate transaminase (GOT) over glutamic pyruvic transaminase (GPT) (ratio GOT/GPT >1). Most reported cases showed a hepatocellular pattern, although a mixed pattern or even a cholestatic pattern can rarely occur [13]. Marked elevations of aminotransferases (up to 100× the upper limit of normal) have been reported, generally in patients presenting with DKA.…”
Section: Discussionmentioning
confidence: 99%
“…GH is associated with the following patterns of abnormal liver enzymes: Elevations in ALT and AST in out of proportion to ALP and bilirubin indicating predominant hepatocellular injury [ 13 , 16 , 18 ]. AST is higher than ALT [ 19 ]. Synthetic function of the liver is preserved, that is, normal albumin and INR levels [ 13 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…GH is usually noted to have aminotransferases elevated about 13 times the upper normal limit [ 19 ]. Our patient had a pattern of liver enzymes similar to that described above.…”
Section: Discussionmentioning
confidence: 99%